Fungal suppressive activities of selected rhizospheric Streptomyces spp. isolated from Hylocereus Polyrhizus / Kamalanathan Ramachandaran - Ramachandaran, Kamalanathan (2014)

(untitled)
Actinomycetes, mainly Streptomyces spp., have been extensively studied as potential biocontrol agents against plant pathogenic fungi. This study was aimed at isolating and screening Streptomyces strains from rhizosphere soils of Hylocereus polyrhizus collected in Kuala Pilah for potential in vitro antifungal activity. A total of 162 putative strains of actinomycetes was isolated from moist-heat treated soil plated on starchcasein-nitrate agar, humic-acid-vitamin agar and raffinose-histidine agar. Based on the ability to produce abundant aerial mycelium, 110 strains were categorised as Streptomycete-like. Seven main groups based on aerial mycelium colour observed in this study were grey (41.4%), white (37.7%), brown (8.0%), orange (4.3%), yellow (4.3%), green (2.5%) and black (1.9%). Three pathogenic fungi, namely, Fusarium semitactum, Fusarium decemcellulare and Fusarium oxysporum were isolated from the diseased stem regions of Hylocereus polyrhizus. The actinomycetes were screened for in vitro antagonistic activity against the isolated pathogenic fungi. In the qualitative screening, 23 strains were able to inhibit at least one of the three pathogenic fungi. In the quantitative screening, three strains, C17, C68 and K98, showed the highest antagonistic activity (70-89%) against all the fungal pathogens. Based on phenotypic and genotypic characterisation, the three selected actinomycete strains were identified as Streptomyces malaysiensis (C17), Streptomyces cavourensis subsp. cavourensis (C68) and Streptomyces sanyensis (K98). Antifungal metabolites produced in agar cultures of the selected isolates caused folding back, stunted and bulging of the mycelium of the pathogens. The selected strains produced a range of different metabolites in International Streptomyces Project (ISP 2) agar medium. The compounds were identified as geldanamycin, bafilomycins (C1, B1 and D), benzoic acid, maltophilin, dihydromaltophilin, 3,5,dihydroxy-2-methyl-benzoic acid, retimycin and lagosin using HPLC-DAD-UV analysis. Phytotoxicity screening showed that spore suspensions of strains Streptomyces malaysiensis and Streptomyces cavourensis subsp. cavourensis were toxic to maize seedlings at both low (1×106 CFU/ml) and high dosage (1×108 CFU/ml) treatments. Meanwhile, the spore suspensions of strain Streptomyces sanyensis promoted the growth of maize seedlings at both low and high dosage treatments. In the greenhouse trials, high dosage (1×108 CFU/ml) treatment of the Hylocereus polyrhizus stems with strain Streptomyces sanyensis spore suspension promoted the total lengths of lateral shoots and longest adventitious roots compared to sterile distilled water treated stems. The application of spore suspension resulted in formation of lateral shoots (93.3%), total length of lateral shoots (767.3%) and the length of the longest adventitious root (75.0%) from day 45 to day 90.